Dyslexia a complete guide for parents and those who help them - Reid, Gavin 1950- (West Sussex, Eng. Wiley-Blackwell, 2011)
"Dyslexia: A Complete Guide for Parents, 2/e is written expressly for parents, and provides the unique insights of a noted educational psychologist on the supportive role parents can play in supporting their dyslexic child. This new edition contains additional sections and up-to-date discussions of current research and programmes.. This new edition contains up-to-date discussions of current research and programmes. The book aims to empower parents by providing them with strategies for dealing with a wide range of concerns. New sections on post-school issues, the emotional needs of young people with dyslexia and sections on how parents can help at home. The information can be applied to all countries and school systems"--Provided by publisher.
"The book empowers parents by offering them the information and support that will allow them to play a vital role in helping their child to thrive and achieve their full potential"--Provided by publisher.
Includes bibliographical references (p.[245]-257) and index.
Keywords: Dyslexic children -- Popular works; Dyslexia -- Popular works